IMPACT OF JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT ON JOB PERFORMANCE IN INDIAN HEALTHCARE INSTITUTIONS - Soni, Reeta; Sharma, Ravinder (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Investment from both the public and commercial sectors is causing a sea change in India’s healthcare system. In an ever-changing environment, the effectiveness of healthcare providers’ work is crucial in determining the standard of treatment and the results achieved by patients. In this study, we look at healthcare workers in India to see how factors like job happiness and organisational commitment affect their productivity on the job. The study seeks to answer the question, "What is the relationship between intrinsic and extrinsic job satisfaction, different types of commitment (affective, continuance, and normative), and organisational and individual performance outcomes?" by drawing on empirical research carried out in hospitals throughout different states in India. In order to maximise efficiency, healthcare organisations should put an emphasis on employee happiness and engagement as there is a significant positive link between work satisfaction, organisational commitment, and job performance.